Antioxidant Activity of β-Glucan. (19th February 2012) - Kofuji, Kyoko; Aoki, Ayumi; Tsubaki, Kazufumi; Konishi, Masanori; Isobe, Takashi; Murata, Yoshifumi
Abstract : β -Glucans extracted from barley, which mainly contains β -(1, 3-1, 4)-D -glucan, are used extensively as supplements and food additives due to their wide biologic activities, including a reduction in blood lipid level. In this study, the antioxidant activity of β -glucan was examined to assess potential new benefits associated with β -glucan, because oxidative stress is considered one of the primary causal factors for various diseases and aging. β -Glucan extracted from barley was found to possess significant antioxidant activity. The amount of antioxidant activity was influenced by different physiologic properties (e.g., structure and molecular size) of β -glucan, which varied depending on the source and extraction method used. The antioxidant activity of β -glucan was significantly higher than that of various polymers that are used as food additives. These results indicate that β -glucan has promise as a polymeric excipient for supplement and food additive with antioxidant and other benefits, which may contribute to enhancing health and beauty.